The Role of Entrepreneurship Training on Business Sustainability (Study on MSMEs Fostered by Rumah BUMN Bandung) - Ryan Fazri Sidiq; Azizah Fauziyah; Ismail Yusuf (Jurnal Indonesia Sosial Teknologi, 2024)
The sustainability of Bandung City MSMEs businesses is an important factor in reducing the problem of unemployment levels and improving the economy of Bandung City. Rumah BUMN Bandung is one of the government's efforts to support the sustainability of Bandung City MSMEs businesses. This research aims to find out how much influence entrepreneurship training has on the business sustainability of MSMEs fostered by Rumah BUMN Bandung. This research focuses on 96 MSMEs fostered by Rumah BUMN Bandung who have actively participated in training, programs or events at Rumah BUMN Bandung at least 3 times. This study using survey method with a descriptive and verification quantitative approach. Data collection was carried out through distributing questionnaires and literature studies. The data analysis technique for this research uses simple linear regression analysis. In Addition, t-test and coefficient of determination were used to test the influence of entrepreneurship training on business sustainability. This research shows that Entrepreneurship Training can influence around 79.3% of the sustainability of UMKN businesses guided by Rumah BUMN Bandung, while 20.7% of the sustainability of UMKM businesses fostered by Rumah BUMN Bandung can be influenced by other factors such as managerial, innovative aspects and external support.